Novel inhibitors of the hepatitis C virus NS3 proteinase - Bennett, Frank; Liu, Yi-Tsung; Saksena, Anil K.; Arasappan, Ashok; Butkiewicz, Nancy; Dasmahapatra, Bimalendu; Pichardo, John S.; Njoroge, F. George; Patel, Naginbhai M.; Huang, Yuhua; Yang, Xiaozheng (Bioorganic & medicinal chemistry letters, 2005)
The hepatitis C virus proteinase inhibitor 4-methyl-1-(phenylmethyl)-2,6-pyridinedione 1 undergoes a novel autoxidation process, on silica gel, leading to the dimer 2 as the major product, a relatively more potent inhibitor of the enzyme.